2011
DOI: 10.1007/s00125-011-2249-7
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of an intracellular metabolic signature impairing beta cell function in the rat beta cell line INS-1E and human islets

Abstract: Aims/hypothesis Chronic hyperglycaemia promotes the progressive failure of pancreatic beta cells in patients with type 2 diabetes mellitus, a clinically highly relevant phenomenon known as glucotoxicity. The intracellular metabolic consequences of a chronically high availability of glucose in beta cells are, as yet, poorly understood in its full complexity. Methods An unbiased metabolite profiling analysis (GCtime-of-flight-MS) was used to identify the time course of core metabolite patterns in rat beta cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…Furthermore, our observation that CART activated CREB in the INS-1 (832/13) cells and rat islets is corroborated by findings from prior studies in neuronal models (15,56,57). Because glucose by itself is known to trigger these signaling pathways in the beta cells (32,58,59), we confirmed that CART indeed activates CREB by starving the cells for an additional 2 h in KRB-H with 2.8 mM glucose after 48 h of glucotoxicity before stimulating with CART. Further, evidence of this pathway being involved in beta cell proliferation comes from in vivo studies showing that beta G s knock-out mice exhibit reduced beta cell mass due to decreased cell prolifera- tion (60).…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, our observation that CART activated CREB in the INS-1 (832/13) cells and rat islets is corroborated by findings from prior studies in neuronal models (15,56,57). Because glucose by itself is known to trigger these signaling pathways in the beta cells (32,58,59), we confirmed that CART indeed activates CREB by starving the cells for an additional 2 h in KRB-H with 2.8 mM glucose after 48 h of glucotoxicity before stimulating with CART. Further, evidence of this pathway being involved in beta cell proliferation comes from in vivo studies showing that beta G s knock-out mice exhibit reduced beta cell mass due to decreased cell prolifera- tion (60).…”
Section: Discussionsupporting
confidence: 77%
“…Protein O-GlcNAcylation is involved in both the physiological regulation of protein function and pathological phe- decreased PFK-1 activity also leads to the diversion of glucose flux from the glycolytic pathway to the pentose phosphate (PPP) or glycogen synthesis pathway. Physiologically, the use of glucose-6-phosphate by these pathways is very limited in β cells (68), yet under pathophysiological conditions, the PPP contributes to the inhibition of β cell function (69) and, hence, could be a contributing factor to defective insulin secretion in CKD. Given that most enzymes in the glycolytic pathway are potentially O-GlcNAcylated (38,70), it is possible that other enzymes are deregulated in addition to PFK-1.…”
Section: Discussionmentioning
confidence: 99%
“…Although this does not establish a causal relationship, it still highlights a marked metabolic difference between cells cultured at low and high glucose, which perform robustly or not in response to physiological stimuli. Exactly how this comes about is unclear, but it is noteworthy that the pentose phosphate pathway has recently been implicated in glucotoxic ␤-cell dysfunction (27). Moreover, this pathway may also play a role in ␤-cell stimulus-secretion coupling (28).…”
Section: Discussionmentioning
confidence: 99%